Multimedia-based Instruction to Increase Achievement in Thai National History of Lower Secondary School Students at Bang Bon District Learning Promotion Centre - ปาละโค รัชนี; วิจิตรวรรณา สมถวิล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) increase academic achievement in Thai history at lower secondary school level before and after learning with multimedia and 2) study learners’ satisfaction with learning using multimedia. It was an experimental research with a one-group pretest-posttest design. The population of the research was lower secondary school students, Bang Bon District Learning Promotion Centre, semester 1, academic year 2024, with 1 classroom, totaling 34 people, to organize learning using multimedia. The research instruments were Learning Plans (3 plans, 8 periods) of using multimedia on Thai history, consisting of multimedia including animated cartoons, computer-assisted instruction, activity sets, a 40-item pre- and post-test achievement test, and a questionnaire on learners’ satisfaction with learning using multimedia. Data were analyzed using basic statistics, including percentage, mean, and standard deviation. The research results according to the objectives found that the learners’ achievement score after learning had percentage of average development was 36.84, and there were 34 students who passed the 75 percent criteria, accounting for 100 percent of all students, and had the highest satisfaction with learning using mixed media at the quality level, higher than the specified quality level.